A NOTE ON BELL POLYNOMIALS AND COLORED PARTITIONS - Alegri, Mateus (2024)
In this short communication we will explore Bell's exponential function in order to obtain new identities for a series involving the function pk(n), the number of partitions of n into k colors. Keywords: k-colored partitions, Convergent series, Bell polynomials.